2022
DOI: 10.1128/spectrum.01578-21
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Drugs Reverse Tet(X)-Conferred Tigecycline Resistance in Gram-Negative Bacteria

Abstract: Recently, high-level tigecycline resistance mediated by tet (X4) and its variants represents a serious challenge for global public health. Antibiotic adjuvant strategy that enhances the activity of the existing antibiotics by using nonantibiotic drugs offers a distinct approach to combat the antibiotic resistance crisis. In this study, we found that bismuth drugs involve bismuth nitrate, a compound previously approved for treatment of stomach-associated diseases, remarkably potentiates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…Since the report of tet (X3/4), the degradative enzyme mechanism has gained more and more attention ( He et al, 2019 ; Xu et al, 2022 ). At present, bismuth drugs and plumbagin can be used as Tet(X) inhibitors to improve the sensitivity of strains to tigecycline, which provides a new therapeutic strategy for the treatment of tigecycline-resistant bacterial infections ( Deng et al, 2022 ; Xu et al, 2022 ).…”
Section: Mechanism Of Tigecycline Resistancementioning
confidence: 99%
“…Since the report of tet (X3/4), the degradative enzyme mechanism has gained more and more attention ( He et al, 2019 ; Xu et al, 2022 ). At present, bismuth drugs and plumbagin can be used as Tet(X) inhibitors to improve the sensitivity of strains to tigecycline, which provides a new therapeutic strategy for the treatment of tigecycline-resistant bacterial infections ( Deng et al, 2022 ; Xu et al, 2022 ).…”
Section: Mechanism Of Tigecycline Resistancementioning
confidence: 99%
“…Multiple recent studies have suggested combination therapy consisting of a tetracycline antibiotic with a TDase inhibitor is also feasible 12 , 33 35 . Park et al reported that anhydrotetracycline can rescue tetracycline efficacy in pathogens expressing Tet(56), a type 2 TDase 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al established that plumbagin, a natural naphthoquinone isolated from plants, shows synergistic effects with tetracycline antibiotics against Tet(X3)-/Tet(X4)-producing bacteria 34 . Deng et al confirmed a combination of Bi(NO 3 ) 3 and tigecycline can prevent development of resistance in bacteria expressing Tet(X) 35 . Most recently, Williford et al reported a series of C9-benzamide and C9-benzylamine anhydrotetracycline analogs that act as bisubstrate inhibitors of type 1 and type 2 TDases 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The same trend was true, although less pronounced, for compound 14 against Tet(X7) (Figure S15). These A variety of TDase inhibitors have been reported, including AZT, 43 bismuth salts, 44 flavonoids, 45 and aTC. 16 The development of selective inhibitors for enzymes in the FMO superfamily has been challenging due in part to the mechanistic complexity, dynamic nature, and substrate flexibility observed for this enzyme class.…”
Section: ■ Results and Discussionmentioning
confidence: 99%